Peningkatan Kapasitas Pokdarwis Dalam Pembuatan Konten Digital Untuk Pemasaran Destinasi Wisata Di Pulau Sebesi: Pengabdian - Supriyanto; Alfina Zsazsa Naqiya; Fakhrur Rozi; Yasinta Amartiwi; Chairunisa; Rendy Kurniawan; Amellia Syahmadi (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Pulau Sebesi, a small island village in Rajabasa Subdistrict, South Lampung Regency, Lampung Province, holds notable tourism potential, including views of Mount Anak Krakatau, snorkeling spots, hiking trails, and authentic coastal community life, and has been officially designated a tourism village by the local government. Despite this potential, the Tourism Awareness Group (Pokdarwis) managing the destination still relies mainly on word-of-mouth promotion and has not optimally utilized digital content to reach prospective visitors, most of whom now search for travel references through social media. This community service program, carried out under the Impactful Student Program of Universitas Indonesia Mandiri, addresses three interrelated gaps identified through field observation: limited technical skills in smartphone photography and videography, weak destination storytelling and copywriting ability, and the absence of a consistent content calendar and social media management practice. Using a community-based tourism approach combined with participatory training, the program guided Pokdarwis members through six stages, namely asset mapping, photography and videography training, storytelling and copywriting training, social media management training, content production and publication, and evaluation with sustainability planning, over an eight-week mentoring period. A custom-developed digital platform, comprising a Digital Content Archive, Content Scheduler, and Engagement Dashboard, supported the organization, scheduling, and monitoring of promotional content. Results show a ten to twelve percent increase in social media reach within three months, with approximately fifty-five percent of members able to independently produce content and sixty percent of uploads demonstrating improved visual and narrative quality. The program illustrates how strengthening community-based digital content creation capacity can enhance tourism destination visibility while also serving as a communication channel for disaster preparedness in a volcano-adjacent coastal setting.